Effects of L-arginine supplementation on plasma lactat and ammonia removal in highly trained runners - Alvares, T.; Marques, A.; Batista, D.; Conte-Junior, C.; Silva, J.; Paschoalin, V. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
L-arginine has been used to promote an increase in blood perfusion in the active muscle, and supposedly increasing the removal of metabolites, such as lactate and ammonia, which are related to exercise fatigue during intense physical exercise. Therefore, the aim of this study was to analyze changes on plasma lactate and ammonia concentrations in response to exercise after L-arginine supplementation. Methods: 15 highly trained runners (4 females) were randomly divided in ARG (6 g of Larginine) and PLA (6 g of corn starch) groups. At the first, the runners took the supplementation and rested for 20 min. Afterwards, the subjects performed two bouts of a 5 km time-trial running test with a 10-min rest period. Blood samples were drawn before supplementation (T0), immediately after the first 5 km time-trial running test (T1), immediately after the second 5 km time-trial running test (T2) and after 20 min of rest (T3). Plasma lactate and ammonia were detected (in duplicate) by spectrophotometry at 450 and 570 nm, respectively. Two-way ANOVA with repeated measures was performed in order to identify differences between groups in plasma lactate and ammonia concentrations on the four time point in which measurements were taken. Results: Significant increases in plasma lactate and ammonia from T0 to T1 and T2 (P<0.01) in both ARG and PLA groups with no significant change between the groups. However, a significant reduction (P<0.01) on plasma lactate and ammonia were observed from T2 (1.78±0.57 mM lactate; 179.1±101.0 ìmol/L ammonia) to T3 (0.80±0.21 mM lactate; 79.73±78.14 ìmol/L ammonia) only in ARG group. Discussion: In both ARG and PLA groups, lactate and ammonia increased significantly in response to exercise. However, during the recovery period of the 5 km time-trial running test, the removal of lactate and ammonia were higher only in ARG. Previous evidence (Denis et al., 1991) has shown positive effect of L-arginine in reducing the exercise-induced hyperammoniemia after 15 min of cycle ergometer exercise. Furthermore, the significant decreases on plasma lactate and ammonia in ARG group may be related with the possible effect of L-arginine on increasing blood perfusion as show by early evidence (Alvares et al., 2012). Although increases in the removal of plasma lactate and ammonia on ARG group were detected, they were not significantly different from PLA group.